Safe Transcatheter Aortic Valve Replacement in a Patient with a Highly Mobile Aortic Valve Mass - Agbor-Etang, Brian B.; Mukherjee, Ashis; Sethi, Prabhdeep S.; Pai, Ramdas G. (International Journal of Angiology, 2018)
Some cardiac valve masses may have embolic potential with worrisome consequences. We describe the dilemmas of and solutions for a highly mobile papillary fibroelastoma on the aortic valve in a nonsurgical patient undergoing transcatheter aortic valve replacement. It was performed safely. The potential strategies to minimize the risk of embolization are discussed.
Keywords: cardiac; aortic valve